Youth Unemployment and Violent Mobilization in Kebbi State - Musa, Aminu; Abdullahi, Danjuma; Baba, Yahaya T. (International Journal of Social and Administrative Sciences, 2017)
Youth unemployment has been the thorny issue affecting our young democracy in Nigeria. Though previous literatures mainly discuss the problems of unemployment without touching on how it instigates violence mobilization. This indicates existence of a missing gap and therefore, this study intends to cover that gap. Data were sourced through interviews conducted with the stake holders such as staff of the electoral institution, civil society, and security agencies such as the Police, Nigerian Security and Civil Defence Corps as well as Nigerian Prisons Service and Nongovernmental Organizations such as Vigilante group. The findings shows that laziness, dying heart, desire to acquire wealthy things simply are the major causes of youth unemployment. The paper gives some recommendations on solving youth unemployment in Kebbi State and indeed Nigeria at large.